The Kantian aesthetic from knowledge to the avant-garde - Crowther, Paul. (Oxford : Oxford University Press, 2010)
This study explains the kind of perceptual knowledge involved in aesthetic judgments. It does so by linking Kant's aesthetics to a critically upgraded account of his theory of knowledge. By describing examples of aesthetic judgment, it is shown that these judgments must involve categories and fundamental schemata.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Kant, Immanuel, -- 1724-1804.; Kant, Immanuel, -- 1724-1804 -- Aesthetics; Aesthetics; Art -- Philosophy